SA-14 Fracture of the Infraglenoid Tubersity in Canine - Rama Arge Frismana; Albiruni Haryo; Hendrik Saputra (Hemera Zoa, 2018)
INTRODUCTIONA broken bone or which was usually called bone fracture had been a medical condition in which there was an incomplete or complete break in the continuity of the bone. There are many different kinds of fracture. The Glenoid Fracture of Os scapula is a very rare occurrence that these fractures have only been described in some series of cases often as a part of scapular fracture series, therefore it was difficult to interpret (1).                In most incidents of ligaments or tendon injuries, fracture or luxation was involved (2). Tuber glenoid fracture often occurs in juvenile animals, it’s because they are very lively and often caused following faulty landing to a jump (3).